Food nanoemulsions: how simulated gastrointestinal digestion models, nanoemulsion, and food matrix properties affect bioaccessibility of encapsulated bioactive compounds - Milinčić, Danijel D.; Salević-Jelić, Ana S.; Kostić, Aleksandar Ž.; Stanojević, Slađana P.; Nedović, Viktor; Pešić, Mirjana B. (Critical reviews in food science and nutrition, 2024)
Food nanoemulsions are known as very effective and excellent carriers for both lipophilic and hydrophilic bioactive compounds (BCs) and have been successfully used for controlled delivery and protection of BCs during gastrointestinal digestion (GID). However, due to sensitive and fragile morphology, BCs-loaded nanoemulsions have different digestion pathways depending on their properties, food matrix properties, and applied models for testing their digestibility and BCs bioaccessibility. Thus, this review gives a critical review of the behavior of encapsulated BCs into food nanoemulsions during each phase of GID in different static and dynamic in vitro digestion models, as well as of the influence of nanoemulsion and food matrix properties on BCs bioaccessibility. In the last section, the toxicity and safety of BCs-loaded nanoemulsions evaluated on in vitro and in vivo GID models have also been discussed. Better knowledge of food nanoemulsions' behavior in different models of simulated GI conditions and within different nanoemulsion and food matrix types can help to standardize the protocol for their testing aiming for researchers to compare results and design BCs-loaded nanoemulsions with better performance and higher targeted BCs bioaccessibility. Food nanoemulsions are effective and excellent carriers for bioactive compounds (BCs). Nanoemulsions are often subject to morphological and structural changes during digestion. BC-s loaded nanoemulsions have different digestion pathways in different digestion models. BC-s have different bioaccessibility in different nanoemulsion models. Food matrix can affect the bioaccessibility of BCs entrapped in nanoemulsions.